The pursuit of happiness : black women, diasporic dreams, and the politics of emotional transnationalism - Williams, Bianca C., 1980- (Online access with subscription: Duke University Press., 2018)
In The Pursuit of Happiness Bianca C. Williams traces the experiences of African American women as they travel to Jamaica, where they address the perils and disappointments of American racism by looking for intimacy, happiness, and a connection to their racial identities. Through their encounters with Jamaican online communities and their participation in trips organized by Girlfriend Tours International, the women construct notions of racial, sexual, and emotional belonging by forming relationships with Jamaican men and other "girlfriends." These relationships allow the women to exercise agency and find happiness in ways that resist the damaging intersections of racism and patriarchy in the United States. However, while the women require a spiritual and virtual connection to Jamaica in order to live happily in the United States, their notion of happiness relies on travel, which requires leveraging their national privilege as American citizens. Williams's theorization of "emotional transnationalism" and the construction of affect across diasporic distance attends to the connections between race, gender, and affect while highlighting how affective relationships mark nationalized and gendered power differentials within the African diaspora.